Tecendo Sonhos com Fios de Resistência: o caso das Mulheres Rendeiras do Assentamento Maceió - Itapipoca/CE - Gomes, Debir Soares (2014)
The studies focused on the relations between genders in the rural areas reveal that the women act more and more in the development of sustainable production systems, in the transformation of economy, in the appreciation of their work and in the recognition of their role as a social subject for the social, economic, environmental and political development of the rural spaces.This work raises reflections about the organization of the lace-making women of the Maceió Settlement, located 60 km from the headquarters of the Itapipoca county and approximately 200 km from the city of Fortaleza, capital of Ceará State. Directly envolved in political, economic and social problems, that affect the environmental resources of the community, tey act on three fronts of distinct actions: on the maintenance of the culture of the lacemaking craft activity; on the defense of a free beach through the occupation and the construction of a camp in a coastal strip of land submitted to estate speculation; and, in the planning and execution of a productive project that involves the management and cultivation of seaweed. Through a qualitative metodology, employing the method of Case Studying and techniques of semi-structured interviews and participant observation, the general objective of this study is to investigate how is the organization of lace-making women of the group “Weaving Dreams”, through the meanings assigned to their social, economical, political, cultural, environmental actions in the construction of a peasant territory. In this perspective, the seeked specific objectives are: to build the trajectory of the group, its history, ogranization and struggle; Identify the references that guide the symbolic dimension of the actions of the women; Analyze the motivations that mobilize the women to alternate and update their actions in the group. The discussion about the construction of the peasant territory is brought to debate by the types of inclusion in the spaces of power by the women and by the struggles that involve the contruction of territorialities. Collectively ogranized, the women produce a material value, but mainly, symbolic, to relate their craftsmanship of lacemaking with a peasant territorialization.